2022
DOI: 10.1111/maps.13811
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated chemical and microstructural analyses of presolar silicate grains from AGB/RGB stars and supernovae in the CO3.0 chondrite Dominion Range 08006

Abstract: We report the structural and chemical analyses of six presolar silicate grains identified in situ in the CO3.0 carbonaceous chondrite Dominion Range (DOM) 08006. Two of the grains have O‐isotopic compositions consistent with origins in the circumstellar envelopes of low‐mass (<2M☉) asymptotic giant branch (AGB)/red giant branch (RGB) stars, although without Mg‐isotopic data, origins in supernovae (SNe) cannot be ruled out. The other four grains have O‐isotopic compositions consistent with origins in the ejecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 133 publications
1
14
0
Order By: Relevance
“…Electron transparent (<100 nm in projected thickness) cross-sections of four grains were prepared using the Thermo Fisher Scientific (formerly FEI) Helios G 3 focused-ion beam scanning-electron microscope (FIB-SEM) located in the Kuiper Materials Imaging and Characterization Facility (KMICF) at the Lunar and Planetary Laboratory (LPL), University of Arizona. The general procedure for producing electron transparent cross-sections of presolar grains is described in several previous papers (e.g., Haenecour et al, 2019Haenecour et al, , 2020Holzapfel et al, 2009;Seifert et al, 2022c;Zega et al, 2007Zega et al, , 2011Zega et al, , 2014bZega et al, , 2015Zega et al, , 2020. Briefly, we first go through an alignment procedure, described in detail in Seifert et al (2022c) to ensure that we capture the presolar grain identified in the NanoSIMS with our FIB transect.…”
Section: Sample and Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Electron transparent (<100 nm in projected thickness) cross-sections of four grains were prepared using the Thermo Fisher Scientific (formerly FEI) Helios G 3 focused-ion beam scanning-electron microscope (FIB-SEM) located in the Kuiper Materials Imaging and Characterization Facility (KMICF) at the Lunar and Planetary Laboratory (LPL), University of Arizona. The general procedure for producing electron transparent cross-sections of presolar grains is described in several previous papers (e.g., Haenecour et al, 2019Haenecour et al, , 2020Holzapfel et al, 2009;Seifert et al, 2022c;Zega et al, 2007Zega et al, , 2011Zega et al, , 2014bZega et al, , 2015Zega et al, , 2020. Briefly, we first go through an alignment procedure, described in detail in Seifert et al (2022c) to ensure that we capture the presolar grain identified in the NanoSIMS with our FIB transect.…”
Section: Sample and Experimental Methodsmentioning
confidence: 99%
“…The general procedure for producing electron transparent cross-sections of presolar grains is described in several previous papers (e.g., Haenecour et al, 2019Haenecour et al, , 2020Holzapfel et al, 2009;Seifert et al, 2022c;Zega et al, 2007Zega et al, , 2011Zega et al, , 2014bZega et al, , 2015Zega et al, , 2020. Briefly, we first go through an alignment procedure, described in detail in Seifert et al (2022c) to ensure that we capture the presolar grain identified in the NanoSIMS with our FIB transect. Next, using the electron beam, we deposited protective Pt fiducial markers on top of the grain and rectangular 200 nm × 100 nm thick markers on either side of the grain fiducial to assist in the thinning process.…”
Section: Sample and Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The procedure followed is a variation of that reported by Zega et al (2007), but we briefly describe it here. For the first two sections extracted, we deposited a thin layer of Pt (200-300 nm) using the electron beam (e-beam) for ease of locating the ROI in the secondary-electron image produced by the Ga + ion beam (i-beam; Seifert et al, 2022;Zega et al, 2020). The thin Pt layer also serves to protect the surface from irradiation by the i-beam during the initial alignment process.…”
Section: Sample and Methodsmentioning
confidence: 99%